Cardiovascular diseases, risk factors and barriers in their prevention in Croatia - Džakula, Aleksandar (Array, 2009)
Summary: Cardiovascular diseases are the leading cause of death in Croatia, with significant regional differences. Despite high mortality rates, high prevalence of various cardiovascular risk factors and well organized public health network, comprehensive system for cardiovascular disease monitoring and interventions does not exist. In this study we analyzed legislation framework and responsibilities of stakeholders relevant for cardiovascular disease surveillance and prevention. According to the international experiences we analyzed characteristics of cardiovascular disease prevention in Croatia and causes of the problems appeared in the preventive programs in Croatia. Analysis showed that primary problem is not inefficiency, but the existence of barriers in preventive activities definition, responsibilities distribution and task implementation. Main cause for such situation is incompatibility of the existing practices in clinical medicine and public health with recommendations from other countries. For the successful prevention of cardiovascular disease in Croatia at least three changes need to be made – define new terms and contents of prevention, define new responsibilities distribution and provide equity in health as basic criterion for successful preventive programs